A STUDY OF ARTHAVAVAHA SROTAS WITH SPECIAL REFERENCE TO MAITHUNA ASAHISHNUTHA (DYSPAREUNIA) - Gopal, *Uma B; H N, Swapna (AYUSHDHARA, 2017)
Understanding the science of Ayurveda is based on proper concept of Tridosha – the Vata, Pitta and Kapha, as these form the physiological control factors. Prakruti, the biological or genetic constitution to a great extent influences each individual, in the way he is, the way he behaves, the way he reacts to certain things there by making a person unique and distinct from one-another. Acharya Sushruta the pioneer in the field of Shareera has gone through evaluating the anatomical structures under the name of Sroto-Shareera, which includes Srotas of Ahara, Dhatu, Mala and Upadhatu like Arthavavaha Srotas. Arthavavahasrotas gets originated from Garbashaya and Arthavavaha Dhamani injury to Arthavavahasrotas results in Vandhyathva, Nastarthava and Maitunaasahisnutha. In his purview it is the local injury to organs of reproductive system which may be due to excessive coitus, repeated curettage, LSCS and thereby, which may result in pelvic adhesions, local infections, tubal block, etc. ultimately leading to Maithunaasahishnutha (dyspareunia). In this study 20 women who were diagnosed as Maitunaasahisnutha selected for assessment of predominant Prakruti based on physiological and anatomical triats. From the statistical analysis it is evident that Kaphaprakruti were more prone for Maithunaashasinutha.